2014
DOI: 10.3390/rs6031827
|View full text |Cite|
|
Sign up to set email alerts
|

A New Metric for Quantifying Burn Severity: The Relativized Burn Ratio

Abstract: Satellite-inferred burn severity data have become increasingly popular over the last decade for management and research purposes. These data typically quantify spectral change between pre-and post-fire satellite images (usually Landsat). There is an active debate regarding which of the two main equations, the delta normalized burn ratio (dNBR) and its relativized form (RdNBR), is most suitable for quantifying burn severity; each has its critics. In this study, we propose and evaluate a new Landsat-based burn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
288
1
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(331 citation statements)
references
References 30 publications
17
288
1
25
Order By: Relevance
“…Next, we computed dNBR, Relative dNBR (RdNBR) (Miler and Thode, 2007) and Relativized Burn Ratio (RBR) (Parks et al, 2014) and denoted them respectively by dNBR_L, RdNBR_L, and RBR_L…”
Section: Methodsmentioning
confidence: 99%
“…Next, we computed dNBR, Relative dNBR (RdNBR) (Miler and Thode, 2007) and Relativized Burn Ratio (RBR) (Parks et al, 2014) and denoted them respectively by dNBR_L, RdNBR_L, and RBR_L…”
Section: Methodsmentioning
confidence: 99%
“…Habitualmente se considera que los intervalos de RdNBR son más consistentes para su extrapolación a otros incendios distintos a donde fueron calibrados (Miller et al, 2009;Cansler and McKenzie, 2012;Parks et al 2014), especialmente para el umbral que separa las clases de moderada y alta severidad, y se aduce como argumento la falta de relación entre RdNBR y NBR pre. En nuestro caso, esa ausencia de relación se dio entre dNBR y NBR pre y entre RdNBR y NBR pre, ya que estos últi-mos presentaron una débil correlación (R 2 = 0,205).…”
Section: Discusión Y Conclusionesunclassified
“…In addition, permafrost thawing has been known to cause erosion, disappearance of lakes, landslides, and ground subsidence (e.g., [6,9,12]). In a study using airborne LiDAR, Jones et al [29] assessed fire-induced thermokarst development and concluded that in regions with ice-rich permafrost in the Arctic, the impact of tundra fires for initiating widespread thermokarst development is greater than what has been estimated to so far.…”
Section: Introductionmentioning
confidence: 98%